2023
DOI: 10.1038/s41467-023-35951-0
|View full text |Cite
|
Sign up to set email alerts
|

Complementary peptides represent a credible alternative to agrochemicals by activating translation of targeted proteins

Abstract: The current agriculture main challenge is to maintain food production while facing multiple threats such as increasing world population, temperature increase, lack of agrochemicals due to health issues and uprising of weeds resistant to herbicides. Developing novel, alternative, and safe methods is hence of paramount importance. Here, we show that complementary peptides (cPEPs) from any gene can be designed to target specifically plant coding genes. External application of synthetic peptides increases the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…[112] In addition to expand our F I G U R E 3 Application of small proteins introduces a system for symbiont effector analysis-informed crop stress adaption and overall fitness improvement. Complementary protein (cPEP) application increases, for example, target transcription and improves crop fitness, [113] which can be informed based on symbiont effector targets with beneficial stress tolerance or growth function. The application of effectors represents a potential strategy to improve plant fitness and effectiveness of fertilizers to address environmental challenges and protect crops.…”
Section: Strategies To Identify and Use The Genetic Potential Of Symb...mentioning
confidence: 99%
See 4 more Smart Citations
“…[112] In addition to expand our F I G U R E 3 Application of small proteins introduces a system for symbiont effector analysis-informed crop stress adaption and overall fitness improvement. Complementary protein (cPEP) application increases, for example, target transcription and improves crop fitness, [113] which can be informed based on symbiont effector targets with beneficial stress tolerance or growth function. The application of effectors represents a potential strategy to improve plant fitness and effectiveness of fertilizers to address environmental challenges and protect crops.…”
Section: Strategies To Identify and Use The Genetic Potential Of Symb...mentioning
confidence: 99%
“…In this respect, a recent technical study suggested simple spraying or watering of plants with complementary peptides (cPEP) from any gene to increase target protein abundance resulting for example in improved growth and heat stress tolerance without genetic modification. [113] The cPEP method is based on findings, that short peptides produced in planta interact with their nascent RNA sequences. [113,114] Ormanecy et al (2023) showed that peptides with 5-40 amino acids in size increased target activity with strong specificity.…”
Section: Strategies To Identify and Use The Genetic Potential Of Symb...mentioning
confidence: 99%
See 3 more Smart Citations